Green Solutions for Degradation of Pollutants - Agarwal, Neha; Jonnalagadda, Sreekantha B.; Solanki, Vijendra Singh (Bentham Science Publishers, 2024)
Green Solutions for Degradation of Pollutants is a compilation of reviews on environmental remediation by sustainable techniques. The book helps readers understand the potential of such techniques in resolving the growing problem of environmental pollutants. The editors have compiled 13 comprehensive reviews on green remediation techniques such as microbial bioremediation, nano-bioremediation, phytoremediation, and green-nanoremediation for the remediation of a variety of pollutants, including wastewater, microplastics, metals and other contaminants. Materials highlighted in the chapters include carbon quantum dots, plant extracts, metallic and organic nanoparticles. Green Solutions for Degradation of Pollutants is a reference book for readers who need to comprehend the practical application of green remediation techniques. Readership Scholars and environmentalists seeking to enhance their knowledge on green and sustainable solutions for a healthy environment and safe society.